The Oncogenic and Tumor Suppressive Functions of the Long Noncoding RNA MALAT1: An Emerging Controversy - Chen, Qingjuan; Zhu, Chenjing; Jin, Yingying (Frontiers in Genetics, 2020)
Long noncoding RNAs are emerging as critical regulators of tumorigenesis. Originally regarded as a pre-mRNA splicing regulator, the long noncoding RNA MALAT1 has been demonstrated to regulate gene transcription by binding histone modification enzymes and transcription factors, and to regulate mRNA and protein expression post-transcriptionally by binding miRNAs and acting as a sponge. Early studies consistently report that MALAT1 is up-regulated in human cancer tissues of various organ origins, particularly metastatic cancer tissues, that high levels of MALAT1 expression in cancer tissues correlate with poor patient prognosis, and that MALAT1 induces cancer cell proliferation, migration and invasion in vitro and tumor metastasis in mice. By contrast, by analyzing multiple independent large datasets, MALAT1 have very recently been found to be down-regulated in human colorectal and breast cancer tissues, and a low level of MALAT1 is associated with decreased patient survival. By binding to the transcription factor TEAD, MALAT1 suppresses metastasis gene expression, colorectal and breast cancer cell migration, invasion and metastasis in vitro and in mice. MALAT1 has therefore been proposed to function as a tumor suppressor in colorectal and breast cancers. More comprehensive studies with multiple independent cohorts of human cancer tissues of various organ origins, in vitro and in vivo function and mechanism studies with rescue experiments are required to confirm the oncogenic or tumor suppressive role of MALAT1 in other cancers.